Directions in Western Canadian Print Making - Eckhardt, Ferdinand; Harff, Llli-Maria (Winnipeg : The Winnipeg Art Gallery, 1968)
Bates, Maxwell ; Bates, Pat Martin ; Esler, John ; Hone, McGregor ; Leathers, Winston ; Nicoll, Marion ; Onley, Toni ; Piddington, Helen V. ; Schmidt, Marianna ; Snow, John
Directions in Western Canadian Print Making, The Winnipeg Art Gallery, Winnipeg, march 7-31, 1968
Catalogue with original work of Winston Leathers
boek